2017
DOI: 10.1016/j.chest.2017.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive Sleep Apnea and Diabetes

Abstract: OSA is a chronic treatable sleep disorder and a frequent comorbidity in patients with type 2 diabetes. Cardinal features of OSA, including intermittent hypoxemia and sleep fragmentation, have been linked to abnormal glucose metabolism in laboratory-based experiments. OSA has also been linked to the development of incident type 2 diabetes. The relationship between OSA and type 2 diabetes may be bidirectional in nature given that diabetic neuropathy can affect central control of respiration and upper airway neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
328
1
14

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 459 publications
(349 citation statements)
references
References 125 publications
(193 reference statements)
6
328
1
14
Order By: Relevance
“…It has already been shown that sleep apnea is associated with hypertension and cardiovascular disease . It is also associated with diabetes, even in an Asian population . Our study added further evidence of these associations in adults aged ≥65 years.…”
Section: Discussionsupporting
confidence: 76%
“…It has already been shown that sleep apnea is associated with hypertension and cardiovascular disease . It is also associated with diabetes, even in an Asian population . Our study added further evidence of these associations in adults aged ≥65 years.…”
Section: Discussionsupporting
confidence: 76%
“…[7][8][9] Although the causal links between sleep disturbances, obesity and glucose dysregulation are not fully understood, experimental studies have improved our understanding of pathophysiologic and mechanistic pathways that underpin this association. [10][11][12] Short-term laboratory-based experiments in young healthy adults have provided convincing evidence that sleep restriction and sleep fragmentation lead to an increase in sympathetic nervous system activity, glucose dysregulation, insulin resistance, alterations in orexigenic and anorexigenic hormones, and excess food intake, ultimately increasing the risk of obesity. [12][13][14][15] Population-based longitudinal studies have also revealed a significant association between sleep duration and obesity in youth.…”
Section: Resultsmentioning
confidence: 99%
“…From a pathophysiologic standpoint, sleep restriction and fragmentation can increase sympathetic nervous system activity, leading to a decrease in insulin sensitivity . Activation of the hypothalamic‐pituitary‐adrenal axis with resulting elevation of evening cortisol can also decrease insulin sensitivity . However, it is important to note that studies of sleep manipulation have been short in duration and performed predominantly in healthy young adults.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent state of the science review of OSA and diabetes 60 included the three studies discussed above with four additional small studies with 23 to 64 participants. This review concluded that the available conflicting evidence regarding the effect of CPAP on glucose metabolism suggests that further study is needed to answer this question.…”
Section: Discussionmentioning
confidence: 99%